The Complete Chloroplast Genomes of Six Ipomoea Species and Indel Marker Development for the Discrimination of Authentic Pharbitidis Semen (Seeds of I. nil or I. purpurea) - Park, Inkyu; Yang, Sungyu; Kim, Wook J.; Noh, Pureum; Lee, Hyun O.; Moon, Byeong C. (Frontiers in Plant Science, 2018)
Ipomoea L. is the largest genus within the Convolvulaceae and contains 600–700 species. Ipomoea species (morning glories) are economically valuable as horticultural species and scientifically valuable as ecological model plants to investigate mating systems, molecular evolution, and both plant–herbivore and plant–parasite interactions. Furthermore, the dried seeds of I. nil or I. purpurea are used in Korean traditional herbal medicines. In this study, chloroplast (cp) genomes were sequenced from six Ipomoea species, namely, I. nil and I. purpurea and, for the first time, I. triloba, I. lacunosa, I. hederacea, and I. hederacea var. integriuscula. The cp genomes were 161,354–161,750 bp in length and exhibited conserved quadripartite structures. In total, 112 genes were identified, including 78 protein-coding regions, 30 transfer RNA genes, and 4 ribosomal RNA genes. The gene order, content, and orientation of the six Ipomoea cp genomes were highly conserved and were consistent with the general structure of angiosperm cp genomes. Comparison of the six Ipomoea cp genomes revealed locally divergent regions, mainly within intergenic spacer regions (petN-psbM, trnI-CAU-ycf2, ndhH-ndhF, psbC-trnS, and ccsA-ndhD). In addition, the protein-coding genes accD, cemA, and ycf2 exhibited high sequence variability and were under positive selection (Ka/Ks > 1), indicating adaptive evolution to the environment within the Ipomoea genus. Phylogenetic analysis of the six Ipomoea species revealed that these species clustered according to the APG IV system. In particular, I. nil and I. hederacea had monophyletic positions, with I. purpurea as a sister. I. triloba and I. lacunosa in the section Batatas and I. hederacea and I. hederacea var. integriuscula in the section Quamoclit were supported in this study with strong bootstrap values and posterior probabilities. We uncovered high-resolution phylogenetic relationships between Ipomoeeae. Finally, indel markers (IPOTY and IPOYCF) were developed for the discrimination of the important herbal medicine species I. nil and I. purpurea. The cp genomes and analyses in this study provide useful information for taxonomic, phylogenetic, and evolutionary analysis of the Ipomoea genome, and the indel markers will be useful for authentication of herbal medicines.